Дефіцит вітаміну D: медичні, молекулярнобіологічні та фармакологічні аспекти - Шварц, Г. Я. (Clinical Endocrinology and Endocrine Surgery, 2009)
This article deals with different forms of vitamin D deficiency and its optimal ways of correction. It specifies the pathway of vitamin D in the body. Besides it explains the correlation between active metabolites of vitamin D and various forms of osteoporosis. A lot of investigations prove the advantage of osteoporosis treatment by active forms of vitamin D (alfacalcidol). It outlined clinical recommendations of Russian Association of Osteoporrosis 2008, concerning usage of active forms of vitamin D.